Does cardiorespiratory fitness moderate the relationship between overweight, cardiovascular risk markers and mental health among forcibly displaced individuals living in a Greek refugee camp? - Gerber, Markus; Filippou, Konstantinia; Knappe, Florian; Morres, Ioannis D.; Tzormpatzakis, Emmanouil; Havas, Elsa; Seelig, Harald; Colledge, Flora; Ludyga, Sebastian; Meier, Marianne; Theodorakis, Yannis; von Känel, Roland; et al. (Frontiers in Sports and Active Living, 2024)
Objectives Refugees may have an increased risk of developing overweight/obesity as they often experience a nutritional transition. Because maintaining good cardiorespiratory fitness can help reduce the negative impact of excess weight on overall health, the objective of this study was to examine whether fitness moderates the relationship between weight status and cardiovascular and mental health outcomes in forcibly displaced individuals living in a Greek refugee camp. Methods A sample of 142 forcibly displaced individuals were recruited. Cardiorespiratory fitness was assessed with the submaximal Åstrand-Rhyming bicycle ergometer test. Blood pressure, blood lipids, blood glucose, and hs-CRP were assessed as physical health outcomes, whereas post-traumatic stress disorder, depression and anxiety symptoms, pain, and quality of life were assessed as mental health outcomes. Main and interaction effects were tested via analyses of covariance (ANCOVAs). Results Almost 50% of the participants were overweight/obese, more than 60% presented with very poor fitness levels, and the percentage of participants with very poor fitness levels was particularly high among overweight/obese participants. Whereas overweight/obesity was associated with a less favorable body composition and cardiovascular risk profile, poor fitness was associated with a higher percentage of body fat and a lower percentage of muscle mass. Cardiorespiratory fitness did not moderate the relationship between overweight/obesity and most of the assessed health outcomes. Conclusions Only limited support was found for the applicability of the fit-but-fat concept to our population of forcibly displaced individuals. Public health services should prioritize measures to prevent overweight/obesity and associated diseases in refugee camps. Moreover, efforts are needed to improve the fitness of camp residents via exercise/sport interventions.